TINJAUAN YURIDIS TENTANG ANAK YANG LAHIR DI LUAR PERKAWINAN MENURUT KEPUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - Amelisa Juliana (JURNAL CIVIL LAW USU, 2013)
Abstrak : Illegitimate child is the child born from the sexual relationships between men and women are not bound by a legal marriage. The birth of a child without marriage preceded by a bond will give the status of the child as a child born outside of marriage, because according to the Marriage Act a marriage can be said to be valid if conducted according to each religion and registered under the laws apply. The decision of the Constitutional Court No. 46/PUU-VIII/2010 that only amplifies the legal status or illegitimate child relationship with the biological father for proven by science eg through DNA test results. Thus the illegitimate child is entitled to alimony, the right lineage and inheritance rights of the biological father. Keywords: Children Foreign Married, Marriage, Constitutional Court  Decision No. 46/PUU-VIII/2010